Efficacy and Safety of Paclitaxel-Based PD-1/PD-L1 Immunotherapies for Triple-Negative Breast Cancer: A Systematic Review and Network Meta-Analysis - Youran Dai; Tianyin Ruan; Wenhui Yang; Shan Liu; Jiahao Chen; Yingying Fang; Qiushuang Li (Clinical Medicine Insights: Oncology)
Background: Triple negative breast cancer (TNBC) is a deadly subtype of breast cancer with limited treatment options. Currently, programmed death 1 (PD-1)/programmed death ligand 1 (PD-L1) inhibitors have become the first choice for breast cancer immunotherapies. Despite paclitaxel being considered a cornerstone drug in breast cancer treatment, the effectiveness, safety, and optimal drug selection for its combination with PD-1/PD-L1 inhibitors remain uncertain. Methods: We conducted a systematic review and network meta-analysis, performing a comprehensive literature search across PubMed, Embase, and the Cochrane Library from the inception of each database through May 18, 2024. Selected trials were those that assessed the efficacy and safety of paclitaxel-based PD-1/PD-L1 therapies for the treatment of TNBC. The primary endpoint assessed was overall survival (OS), while secondary outcomes included progression-free survival (PFS), adverse events (AEs), overall response rate (ORR), and Pathological complete response (pCR). This study is registered in PROSPERO under registration number CRD42023429651. Results: A total of 8 RCTs meeting our eligibility criteria were included, involving 4626 patients who received either Paclitaxel (Paclitaxel-placebo/chemotherapy) or a combination of durvalumab, pembrolizumab, atezolizumab, toripalimab with paclitaxel. The pooled results demonstrated that Durvalumab combined with Paclitaxel significantly reduced the hazard ratio for OS (surface under the cumulative ranking [SUCRA]: 91.05%) and PFS compared with Paclitaxel alone (SUCRA: 83.52%). Additionally, Durvalumab plus Paclitaxel significantly improved the ORR compared with Paclitaxel (odds ratio [OR]: 2.30; 95% credible interval [CrI]: 1.10–5.20). For safety outcomes, Atezolizumab plus Paclitaxel showed a favorable profile in AEs, with no significant differences observed between groups. In the pCR study, Pembrolizumab plus Paclitaxel was the most effective treatment option (SUCRA: 81.85%). Conclusions: When combined with paclitaxel, PD-1/PD-L1 inhibitors exhibit a favorable survival benefit. The combination of Durvalumab and paclitaxel represents the optimal treatment option. In the future, attention should be paid to the TNBC subtypes and drug dosage, as these factors may help to design personalized TNBC treatment programs.